I spy spooky night : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Scholastic, 2005)
Rhyming text challenges the reader to find specific objects in several spooky photographs.
"Cartwheel books."
Elem. School Library Collection
School Library Journal starred
Wilson's Children
Booklist, September 1996
Elem. School Library Collection, June 2000
Keywords: Halloween -- Juvenile literature; Picture puzzles -- Juvenile literature; Riddles, Juvenile; Halloween; Picture puzzles; Halloween; Picture puzzles